Analysis and Calculation of Marginal Electricity Price of Nodes with Network Loss from the Perspective of Intelligent Robot Considering Digital Signal Processing Technology (Informatica, 2024)
With the development of digital integrated circuit, embedded technology and intelligent robot technology, the application of intelligent robot, microprocessor and DSP digital equipment is more and more extensive, and the related system of intelligent robot is also more and more large. This paper mainly introduces the marginal loss of electricity price based on digital signal processing technology. Among them, the loss grid has the advantages of easy mass production and transportation, easy conversion, easy control, low loss, high efficiency, environmentally friendly, etc., has been widely used in today's world. Our traditional power generation industry belongs to the business model of power generation monopoly, transmission and distribution integration. Such systems integrate all aspects of a digital signal into an intelligent robotic unit, which makes business operations and management more difficult. At the same time, the existence of monopoly power companies reduces the production efficiency of enterprises, has a negative impact on the development of enterprises, and then directly affects the development of the whole industry. It is of great significance for the professional management of the company to establish a market-oriented market mechanism to separate the power transmission and distribution of intelligent robots from other aspects and set up corresponding companies. Adopting market-oriented approach can effectively reduce energy consumption, realize the rational allocation of resources, so as to improve the productivity of enterprises and promote the sustainable and healthy development of our economy.